Self-related consequences of death fear and death denial - Cozzolino, Philip, J.; Blackie, Laura E.R.; Meyers, Lawrence, S. (Taylor & Francis, 2013)
This study explores self-related outcomes (e.g., esteem, self-concept clarity, existential well-being) as a function of the interaction between self-reported levels of death fear and death denial. Consistent with the idea that positive existential growth can come from individuals facing, rather than denying, their mortality (Cozzolino, 2006), the authors observed that not fearing and denying death can bolster important positive components of the self. That is, individuals low in death denial and death fear evidenced an enhanced self that is valued, clearly conceived, efficacious, and that has meaning and purpose.